1993
DOI: 10.1038/364818a0
|View full text |Cite
|
Sign up to set email alerts
|

Receptor and protein kinase C-mediated regulation of ARF binding to the Golgi complex

Abstract: The formation of constitutive transport vesicles involves the association of non-clathrin coat proteins to transport organelles. Here we report that IgE receptors and protein kinase C (PKC) regulate the GTP-dependent binding of the two coat proteins ADP-ribosylation factor (ARF) and beta-COP to Golgi membranes in rat basophilic leukaemia cells. Activation of IgE receptors and PKC prevented the ARF and beta-COP dissociation from Golgi membranes that occurs in permeabilized cells in the absence of GTP and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 36 publications
6
93
3
Order By: Relevance
“…eRACK/b'COP binds the small ras-like GTPase, ARF, in its GTP-bound form (De Matteis et al, 1993). The GTP-GDP cycle of ARF is linked to COPI recruitment, vesicle binding, and uncoating (De Matteis et al, 1993). We have shown that increased binding of eRACK to Golgi membranes in the presence of GTPgS is associated with an increase in ePKC binding (Csukai et al, 1997).…”
Section: Viral Proteinsmentioning
confidence: 77%
See 1 more Smart Citation
“…eRACK/b'COP binds the small ras-like GTPase, ARF, in its GTP-bound form (De Matteis et al, 1993). The GTP-GDP cycle of ARF is linked to COPI recruitment, vesicle binding, and uncoating (De Matteis et al, 1993). We have shown that increased binding of eRACK to Golgi membranes in the presence of GTPgS is associated with an increase in ePKC binding (Csukai et al, 1997).…”
Section: Viral Proteinsmentioning
confidence: 77%
“…However, eRACK is part of the coatomer complex, COPI, and therefore binds to a number of other proteins. eRACK/b'COP binds the small ras-like GTPase, ARF, in its GTP-bound form (De Matteis et al, 1993). The GTP-GDP cycle of ARF is linked to COPI recruitment, vesicle binding, and uncoating (De Matteis et al, 1993).…”
Section: Viral Proteinsmentioning
confidence: 99%
“…Therefore, it is feasible that Rap1A directly binds to, and thereby stimulates PLCe in the Golgi apparatus in response to extracellular stimuli such as EGF treatment. Considering that protein kinase C exists in the Golgi apparatus (de Matteis et al, 1993), and can act as a downstream target of DAG yielded by PLCe, the Rap1A/PLCe signaling pathway may provide a link between growth factor receptors and Golgi-localized protein kinase C.…”
Section: Discussionmentioning
confidence: 99%
“…PMA-induced translocation of ARF to the Golgi membrane has already been described [50]. PMA also induced a massive translocation of PKC␣.…”
Section: Discussionmentioning
confidence: 84%